Solvent-Free Microwave Extraction: Analisis Fitokimia Minyak Atsiri Daun Ruku-Ruku (Ocimum tenuiflorum, L.) dan Aktivitas Antibakteri terhadap Escherichia coli - Susanti, Yuni; Ayu Qurota A'yun; Syafaatullah, Achmad Qodim; Melinda Aprilia; Dwi Danang Armadani (Jurnal Teknik Kimia USU, 2025)
Holy basil (Ocimum tenuiflorum, L.) is one of the aromatic herbs that grows in empty or abandoned areas. Previous studies used conventional methods, including maceration and hydrodistillation, to extract Ocimum tenuiflorum, L. Genetic variation, plant phenology, geographical conditions, and extraction techniques affect the yield and variability of essential oil phytochemical composition. Here in, we report essential oil extraction of Ocimum tenuiflorum green and purple using solvent-free microwave extraction. The yield calculation obtained from purple and green O. tenuiflorum essential oils was 2.25 and 2.17%, respectively. GCMS data shows that the phytochemical compounds in Ocimum tenuiflorum essential oils, purple and green leaves, are dominated by sesquiterpene and phenylpropene groups. In the essential oil of purple Ocimum tenuiflorum leaves, the major phytochemical compound components are methyl eugenol, β-Caryophyllene, and Germacrene-D.  Antibacterial activity showed that Ocimum tenuiflorum purple essential oils a more preeminent effect against Escherichia coli than green.